Parenting stress and increased expectations in the early family phase - a barrier to the use of support services? Elternstress und erhöhte Ansprüche in der frühen Familienphase - Ein Hindernis für die Nutzung von Unterstützungsangeboten? - Liese, Désirée; Ulrich, Susanne M.; Löchner, Johanna; Lux, Ulrike (Public Health Forum, 2023)
Parenting stress is widespread and can have a negative impact on family climate and child development. In order to be able to assess the need for support, the significance of parenting stress and barriers to accepting help will be explored. In addition, the study examines which personality traits increase the risk of overload.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Big Five; child health; parenting stress; prevention services; psychosocial burden